Locally perceived hard global constraints in multi-agenty schedulling - Reis, J.; Mamede, N.; O'Neill, H. (Journal of Intelligent Manufacturing, 2001)
We propose how to model enterprise facilities (like factories, warehouses, etc.) in a multi-product production/distribution network, capacity management at those facilities, and scheduling agents which act as enterprise managers, taking decisions that affect the available capacity. A coordination mechanism through which scheduling agents can locally perceive hard global temporal constraints is also proposed.